An Empirical Analysis on the Influencing Elements of IPO Underpricing in China 2003-2007 - wang, zifei (2012)
This paper investigates the phenomenon of Initial Public Offerings underpricing on China A-share market both in Shanghai stock market and Shenzhen Stock ranging from the year 2003 to 2007. Firstly the research indicates that the underpricing of IPO exists in every stock market. Secondly, literature reviews made by western researchers and Chinese researchers would be firstly introduced. Specifically, some important theories would be reviewed, such as signaling hypothesis, winner’s curse hypothesis, and investment bank hypothesis etc. In this part, special features in Chinese stock market would be focused on. Thirdly, it should be interpreted that the data collection and the methodology used in this paper. The research would use multiple liner regression model to analysis underpricing level and investigate some factors that might affect underpricing of IPO. The variable used in the regression should be detail explained and the hypothesis should also be proposed in this part. Next, according to the regression results, it indicates that underpricing in China is serious, and the special Chinese regulations and systems also affect the magnitude of IPO underpricing. Finally, it can be concluded that the influencing elements can affects the level of IPO underpricing phenomenon to some extent. However, the Chinese stock market not mature compared with the developed stock markets.